Antimicrobial Stewardship in General Practice: A Scoping Review of the Component Parts - Lesley Hawes; Kirsty Buising; Danielle Mazza (MDPI AG, 2020)
There is no published health-system-wide framework to guide antimicrobial stewardship (AMS) in general practice. The aim of this scoping review was to identify the component parts necessary to inform a framework to guide AMS in general practice. Six databases and nine websites were searched. The sixteen papers included were those that reported on AMS in general practice in a country where antibiotics were available by prescription from a registered provider. Six multidimensional components were identified: 1. Governance, including a national action plan with accountability, prescriber accreditation, and practice level policies. 2. Education of general practitioners (GPs) and the public about AMS and antimicrobial resistance (AMR). 3. Consultation support, including decision support with patient information resources and prescribing guidelines. 4. Pharmacist and nurse involvement. 5. Monitoring of antibiotic prescribing and AMR with feedback to GPs. 6. Research into gaps in AMS and AMR evidence with translation into practice. This framework for AMS in general practice identifies health-system-wide components to support GPs to improve the quality of antibiotic prescribing. It may assist in the development and evaluation of AMS interventions in general practice. It also provides a guide to components for inclusion in reports on AMS interventions.